Hypertensive woman and the relation with menopause - Zélia Maria de Sousa Araújo Santos; Raimunda Magalhães da Silva; Diana Arruda Monteiro (Rev Rene)
This research is an exploratory study that investigated the relationship of menopause with the arterial hypertension diagnosis, emphasizing health education for the maintenance of the ell-being. 142 hypertensive women participated in the research. They were followed by the Hypertension Out-Patient Clinic at the Public Health Institute, situated in Fortaleza-Ceará. The data was collected during the nursing consultation and analyzed statistically. Among the 142 women, 104 (73%) had reached natural menopause between the ages of 40 to 50 and 42 (29%) had surgical menopause between the ages of 30 to 50, the majority of which, between 36 to 46 years of age. Among women having surgical menopause, only 05 (12%) were submitted to hormonal reposition. Some, 21 (50%) were submitted to simultaneous hysterectomy and oophorectomy. The conclusion of the research was that, there were women that became hypertensive independently of having already entered menopause and the way it happened – natural or surgical.